(3GdeQGLYI GdNGQLjIs (3ehVhYGJ eJNUUIs - (3GdUMf(B, (3YHO GdaJGM eMeOs; (3SejQs ((3GdEScfOQjIs (3OGQ GdLGeYI GdLOjOIs, 2000)
(3Yde GdeQGLYI(B- (3CSGdjH GdeYGjfI GdEMUGFjI aj GdeQGLYI(B- (3GdELQGAGJ GdJMdjdjI aj GdeQGLYI GdaMU GdNGU(B- (3GdeQGLYI GdEOGQjI(B- (3eQGLYI GdHfhc GdJLGQjI(B- (3GdLgGR GdeQcRj ddeMGSHGJ(B- (3GdeQGLYI aj Xd CfXeI GdJTZjd GdEdcJQhfj ddHjGfGJ(B- (3GdeQGLYI GdHjFjI(B.s
Keywords: (3GdEOGQIs; (3GdeMGSHIs; (3GdeQGLYIs